La visión responsable de Javier Marías: una aproximación filosófica a la literatura mariesca a la luz de Julián Marías y Ortega y Gasset - Bertrán, Santiago (The University of Edinburgh, 2018)
This thesis examines the concept of vision in the major novels of Javier Marías in light of the philosophy of José Ortega y Gasset and Julián Marías. Marías’s fictions present us with a series of characters that prove to be acute observers, interpreting the world both to understand it better and to orientate themselves within it. I argue that this hermeneutical approach extends to Marías’s poetics, which reflect two main concepts not yet well studied: on one hand, what Marías, borrowing a term from his father, Julián Marías, calls ‘pensamiento literario’, which describes creative writing as one of the best tools the author has to ‘see’ or understand the real world; and on the other, his concept of ‘reconocimiento’, which defines the sympathetic process by which the reader ‘sees’ or ‘recognises’ him or herself in the narrative. These ‘visual’ poetics reveal a number of epistemological and ethical implications that gesture not towards the postmodern relativism often associated with Marías, but rather towards a modern intellectual paradigm whose possibilities were curtailed after the Civil War.
Keywords: Javier Marías; narration; poetics; Philosophy